2022
DOI: 10.1039/d2nr03076d
|View full text |Cite
|
Sign up to set email alerts
|

Au3-Decorated graphene as a sensing platform for O2 adsorption and desorption kinetics

Abstract: The adsorption and desorption kinetics of molecules is of significant fundamental and applied interest. In this paper, we present a new method to quantify the energy barriers for the adsorption...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
4
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 52 publications
(76 reference statements)
0
4
0
Order By: Relevance
“…Such an approach minimizes the effect of contact resistances. [ 51 ] The sheet resistivity can be calculated as ρsheet=(W/L)(ΔV/IB)${\rho}_{\textit{sheet}} = (W/L)(\Delta V/{I}_{B})$, [ 37,52 ] where normalΔV$\Delta V$ is the measured voltage between the middle contacts, IB${I}_{B}$ is the applied current (i.e., 1 µA), and W$W$ and L$L$ are the width (100 µm) and the length (50 µm) of the probed area, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Such an approach minimizes the effect of contact resistances. [ 51 ] The sheet resistivity can be calculated as ρsheet=(W/L)(ΔV/IB)${\rho}_{\textit{sheet}} = (W/L)(\Delta V/{I}_{B})$, [ 37,52 ] where normalΔV$\Delta V$ is the measured voltage between the middle contacts, IB${I}_{B}$ is the applied current (i.e., 1 µA), and W$W$ and L$L$ are the width (100 µm) and the length (50 µm) of the probed area, respectively.…”
Section: Resultsmentioning
confidence: 99%
“…Yang et al investigated the tunability of palladium decorated graphene, which can be used as formaldehyde detector . Libeert et al showed the high sensitivity of graphene-supported Au 3 cluster for observing the ad- and desorption kinetics of oxygen molecules …”
Section: Introductionmentioning
confidence: 99%
“…showed the high sensitivity of graphene-supported Au 3 cluster for observing the ad-and desorption kinetics of oxygen molecules. 37 The stability analysis of the support anchored clusters helps to select the most prominent models both for the catalyst and sensor material. 38,39 Here, the accurate description of the interaction between the graphene-based support and the clusters is essential, which requires the inclusion of spatially long-range terms.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation